Model Tests of Concrete-Filled Fiber Reinforced Polymer Tube Composite Pile Under Cyclic Lateral Loading - Chao Yang; Guoliang Dai; Weiming Gong; Yuxuan Wang; Mingxing Zhu; Shaolei Huo (Buildings)
Concrete-filled FRP (Fiber Reinforced Polymer) tube composite piles offer superior corrosion resistance, making them a promising alternative to traditional piles in marine environments. However, their performance under cyclic lateral loads, such as those induced by waves and currents, requires further investigation. This study conducted model tests on 11 FRP composite piles embedded in sand to evaluate their behavior under cyclic lateral loading. Key parameters, including loading frequency, cycle count, loading mode, and embedment depth, were systematically analyzed. The results revealed that cyclic loading induces cumulative plastic deformation in the surrounding soil, leading to a progressive reduction in the lateral stiffness of the pile–soil system and redistribution of lateral loads among piles. Higher loading frequencies enhanced soil densification and temporarily improved bearing capacity, while increased cycle counts caused soil degradation and reduced ultimate capacity—evidenced by an 8.4% decrease (from 1.19 kN to 1.09 kN) after 700 cycles under a 13 s period, with degradation rates spanning 8.4–11.2% across frequencies. Deeper embedment depths significantly decreased the maximum bending moment (by ~50%) and lateral displacement, highlighting their critical role in optimizing performance. These findings directly inform the design of marine structures by optimizing embedment depth and load frequency to mitigate cyclic degradation, ensuring the long-term serviceability of FRP composite piles in corrosive, high-cycle marine environments.